Expression of toll-like receptor 2, 4 and related cytokines in intraperitoneally inoculated Balb/C mice with Echinococcus multilocularis - Apaer, Shadike (e-Century Publishing Corporation, 2017)

(untitled) (Int J Clin Exp Pathol)
Immune response pattern between host and Echinococcus multilocularis (E. multilocularis) is considered as a crucial point in development of alveolar echinococcosis (AE). In this study, we are aiming to study the expression patterns of TLR2 and TLR4 with related cytokines and transcription factors in secondary E. multilocularis infected murine model. The murine model of AE was developed by using intraperitoneal inoculation of E. multilocularis protoscolexes and albendazole (E. m+ABZ group) or carboxy methyle cellulose (CMC; E. m+CMC group) administration via gastric tube was initiated in the third month and continued for one month. Mice with CMC administration served as negative controls (C+CMC group). The splenic cells and peritoneal exudates cells (PECs) were prepared and the levels of IFN-γ, IL-10, and IL-5 in splenic cells and PECs culture supernatants were detected using enzyme linked immune-sorbent assay (ELISA). Besides, the mRNA expression levels of TLR2, 4, transcription factors and cytokines were detected by using real-time fluorescent quantitative reverse-transcription polymerase chain reaction (qRT-PCR). The concentration levels of IFN-γ, IL-10, and IL-5 in PECs and splenic cell supernatants were extremely lower, however, significantly elevated after stimulated with Concanavalin A (ConA) for 36 h with higher concentrations in E. m+CMC group comparing to both E. m+ABZ and C+CMC group. The mRNA levels of TLR2, 4 and GATA3, IFN-γ, IL-10 in splenic cells were significantly increased in E. m+CMC group comparing with other groups. Simultaneously, T-bet mRNA expressions were elevated in E. m+ABZ and C+CMC group compared to E. m+CMC group. In addition, T-bet/GATA3 ratios was higher in E. m+ABZ group compared to E. m+CMC group and were higher in C+CMC group than those in E. m+CMC group. TLR2 mRNA expression in splenic cells showed a positive correlation with IL-10 concentration levels in splenic cell culture supernatants. The present study provides evidence on the possible role of TLR2 in the process of immune tolerance during E. multilocularis infection and suggests albendazole treatment might reverse the immune tolerance situation and improve parasite clearance process.